2008
DOI: 10.1007/s10995-008-0359-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Physical Activity Among Pregnant Women

Abstract: Objective-Physical activity generally declines during pregnancy, but barriers to activity during this time period are not well understood. The objective was to examine barriers to physical activity in a large cohort of pregnant women and to explore these barriers in more depth with qualitative data derived from a separate focus group study using a socioecologic framework.Method-A total of 1535 pregnant women (27-30 weeks' gestation) enrolled in the Pregnancy, Infection, and Nutrition Study were asked an open-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
267
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(306 citation statements)
references
References 31 publications
27
267
3
9
Order By: Relevance
“…Other studies have related that non-pregnant women only undertake PA outside of the home during daylight hours (Caperchione et al, 2011), which becomes hard with a day's work, and have also indicated that finding time to be active when not attending to family duties is a major barrier to PA engagement (Caperchione, Mummery, & Joyner, 2009), as family duties create time conflicts. Along the same lines, Evenson et al, (2009) found that 85% of a sample of 1535 pregnant women reported that intrapersonal factors were the main barriers to leisure PA. However, the evaluation moments in this study were different from the evaluation moments in our study (first evaluation at 20 weeks and second evaluation at 27-30 weeks).…”
Section: Barriers To Physical Activity According To the Socioecologimentioning
confidence: 84%
See 3 more Smart Citations
“…Other studies have related that non-pregnant women only undertake PA outside of the home during daylight hours (Caperchione et al, 2011), which becomes hard with a day's work, and have also indicated that finding time to be active when not attending to family duties is a major barrier to PA engagement (Caperchione, Mummery, & Joyner, 2009), as family duties create time conflicts. Along the same lines, Evenson et al, (2009) found that 85% of a sample of 1535 pregnant women reported that intrapersonal factors were the main barriers to leisure PA. However, the evaluation moments in this study were different from the evaluation moments in our study (first evaluation at 20 weeks and second evaluation at 27-30 weeks).…”
Section: Barriers To Physical Activity According To the Socioecologimentioning
confidence: 84%
“…Barriers according to the socioecological framework. All women who said that they engaged in no leisure PA in their first and second trimesters were asked about their reasons for not performing leisure PA. A table with types of barriers to leisure PA was constructed based on Evenson's study (Evenson et al, 2009); it included such possible answers as lack of time, work or social conflicts, being too busy, concern about the baby, not wanting to overdo it, medical necessity, dislike of exercise, lack of motivation, incontinence, lower back pain, pelvic pain, other medical conditions, having no one to exercise with, not having access to enough recreational facilities and not being able to afford such facilities. Participants had to indicate whether each option was considered as a barrier.…”
Section: Assessment Instruments/outcome Measurementioning
confidence: 99%
See 2 more Smart Citations
“…The physical activity goalsetting tool emphasized improving awareness about the safety of exercise during pregnancy because previous research found it to be a barrier to physical activity during pregnancy. [20][21][22] In addition, the tool focused on assessing barriers to being active and identifying strategies specific to those barriers. Below are the steps that were part of the physical activity goal-setting feature:…”
Section: Aim 2: the E-moms Roc Intervention And Its Implementationmentioning
confidence: 99%